2022
DOI: 10.4102/sajhivmed.v23i1.1424
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and HIV viral load suppression in children and adolescents in Durban, South Africa

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic poses challenges to paediatric and adolescent HIV treatment programme. Modelling exercises raised concerns over potential impact of disruptions. Objectives To describe the impact of the COVID-19 pandemic on viral load (VL) testing among infants, children and adolescents on antiretroviral treatment (ART) in Durban, South Africa. Method Routinely collected, aggregated data of monthly V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Furthermore, a systematic review of data from five studies from two high income countries (USA and Italy) consistently showed no significant difference in viral suppression between pre-COVID-19 and COVID-19 period [ 20 ]. Similar findings were observed from studies in Malawi [ 17 ], South Africa [ 18 ], and the United States [ 16 ]. Appointment keeping was however observed to have reduced between pre-COVID-19 and COVID-19 period in an Ethiopian study [ 19 ].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, a systematic review of data from five studies from two high income countries (USA and Italy) consistently showed no significant difference in viral suppression between pre-COVID-19 and COVID-19 period [ 20 ]. Similar findings were observed from studies in Malawi [ 17 ], South Africa [ 18 ], and the United States [ 16 ]. Appointment keeping was however observed to have reduced between pre-COVID-19 and COVID-19 period in an Ethiopian study [ 19 ].…”
Section: Introductionsupporting
confidence: 89%
“…Few studies have evaluated system efficiency and patient outcomes related to HIV care during the COVID-19 pandemic. Some studies have shown a decrease in viral load testing during COVID-19 compared to pre-COVID-19 period [16][17][18]. Viral load turnaround time was also observed to have increased between pre-COVID-19 and during COVID-19 period in a study in North East Nigeria [19].…”
Section: Introductionmentioning
confidence: 99%
“…Even though adolescent data is scanty, studies comparing viral load suppression rate pre-COVID-19 and during the pandemic have generally indicated a decrease in VLS. For instance, a study conducted in Durban, South Africa in 2020 among ALHIV, VLS was 98.5% pre-COVID-19 and dropped to 83.6% during the COVID-19 period [24]. The reduction in VLS was also seen in a study conducted in Atlanta [25].…”
Section: Introductionmentioning
confidence: 81%
“…As a result of the lockdowns, there were disruptions in access to HIV prevention and control services resulting in new infections and severe HIV treatment outcomes, especially among adolescents from SSA [24,26,[32][33][34]. Within SSA, COVID-19 prevention and treatment options were limited with low vaccination coverage of 3% yet COVID-19 infection has been associated with severe outcomes among people living with HIV [1,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These changes in access and utilisation of both preventative healthcare and HIV chronic care raised concerns for negative health consequences, especially where poverty, HIV and Tuberculosis (TB) is common and where many live in high density communities [11]. HIV viral suppression rates, however, were shown to be maintained among children, suggesting some chronic disease programmes remained reasonably robust over this period [12].…”
Section: Introductionmentioning
confidence: 99%